PERANCANGAN APLIKASI MAJELIS GABUNGAN BERBASIS ANDROID (STUDI KASUS MAJELIS NURRUSYSYIFA) - Sitorus, Anwar Tonggo; Alfiansyah, Muhammad (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
The development of Android-based mobile technology has created new opportunities for the digitalization of religious content, including the distribution of Islamic recitation materials. This study aims to design and develop an Android-based “Majelis Gabungan” application for Majelis Nurrusysyifa to address the limited distribution of printed materials such as Yasin, dzikir, ratib, kitab maulid, collections of sholawat, and Asmaul Husna. A descriptive quantitative approach with the Research and Development (R&D) method using the Waterfall model was employed, encompassing needs analysis, design, implementation, testing, and evaluation. Data were collected through observation, questionnaires, and interviews with 30 participants from the congregation. The testing results show that the application achieved an average loading time of 1.23 seconds, 74 MB memory consumption, and good compatibility across various Android devices. User evaluation indicated that 53% of respondents were satisfied and 47% were very satisfied with the application’s performance, with no negative ratings. The application was found to enhance accessibility, engagement, and user satisfaction, while also contributing to paper usage reduction. Therefore, this application serves as an effective solution and has the potential to be replicated in other majelis taklim or religious organizations in Indonesia.